Performance evaluation of mobile wireless communication and services with modelling of real environment. (18th June 2007) - Uchiyama, Akira; Maeda, Kumiko; Umedu, Takaaki; Yamaguchi, Hirozumi; , Teruo Higashino
Recently, several types of services in mobile wireless networks for future ubiquitous society have been proposed. The performance of these services strongly depends on deployment and mobility of network nodes. In this paper, we survey potential services and applications on mobile wireless networks and evaluate their performance with modelling of real environment. For this purpose, we have developed a wireless network simulator 'MobiREAL', which assists developers to model and reproduce movement of network nodes. Experimental results have shown that deployment and mobility considerably affect the performance of services and applications.